Analysis of Leading Sectors in Economic Growth in Malang District - Wijaya, Riko Setya; Asmara, Kiky; Rifani, Siti Khusnul (PT FORMOSA CENDEKIA GLOBAL, 2023)
Leading sectors are those with the ability to strengthen the local economy and generate wealth. Finding the economic sectors that contribute most to the Malang District's regional gross domestic product is the aim of this study. This study uses quantitative description to identify the major and minor sectors of Malang Regency and makes use of time series data as secondary data from 2020 to 2022. Among the analysis instruments employed are the Location Quotient (LQ); The results showed that: (1) According to the location quotient (LQ) analysis, the main sectors of Malang Regency are agriculture, forestry, fisheries, manufacturing, water supply, waste management, solid waste and recycling. It consists of Masu. Construction industry retail and wholesale. repairs for cars, motorcycles, and other vehicles. (2) Shift share analysis for wholesale/retail, automobile/motorcycle repair. It can be seen that the proportional share (PS) and national PR share are highest in trade in goods both wholesale and retail, vehicle and motorcycle repair, and differential sharing. mining and quarrying sector.Leading sectors are those with the ability to strengthen the local economy and generate wealth. Finding the economic sectors that contribute most to the Malang District's regional gross domestic product is the aim of this study. This study uses quantitative description to identify the major and minor sectors of Malang Regency and makes use of time series data as secondary data from 2020 to 2022. Among the analysis instruments employed are the Location Quotient (LQ); The results showed that: (1) According to the location quotient (LQ) analysis, the main sectors of Malang Regency are agriculture, forestry, fisheries, manufacturing, water supply, waste management, solid waste and recycling. It consists of Masu. Construction industry retail and wholesale. repairs for cars, motorcycles, and other vehicles. (2) Shift share analysis for wholesale/retail, automobile/motorcycle repair. It can be seen that the proportional share (PS) and national PR share are highest in trade in goods both wholesale and retail, vehicle and motorcycle repair, and differential sharing. mining and quarrying sector.